Migration Currents and Building Practice Exchanges in the Portuguese Diaspora: From the Algarve to South America and Back - Ricardo Costa Agarez (ABE Journal)
This paper highlights the significance of essential shifts in the social history of the Algarve, in the south of Portugal—namely through currents of migration from specific areas of the region—for our understanding of its built fabric, its traditions and modernisation processes. Traces of parallel developments in “vernacular” building custom in the Algarve and (postcolonial) Brazil during the 1870s, of Algarvian civil engineers building skyscrapers in São Paulo and commissioning modern architecture in Faro (Algarve) in the 1950s, and of Algarvian migrants prospering in Venezuela and becoming developers supporting modernism back home in the 1960s signal the impact of transcontinental migration flows, from Portugal to South America and back, on the creation of a constellation of building practices. Understanding these practices prompts us to push the boundaries of the history of modern European architecture to encompass the agency of non-architect migrants and their many roles. As designers, builders, dwellers and clients, who in some instances influenced the work of key architects while remaining marginal to the historical account of the profession, they were often the conduit of architectural changes that shaped the built environment.